Biocontrol Agents of Phytonematodes 2015
DOI: 10.1079/9781780643755.0217
|View full text |Cite
|
Sign up to set email alerts
|

Nematophagous bacteria as biocontrol agents of phytonematodes.

Abstract: This chapter focuses on live bacterial action towards the plant parasitic nematodes and their economically important host plants. Recent advances used in this field as a background to support future research is also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Importance of biological control of pests is growing, and this is obviously reflected by considerable venture capital in research by multinational firms and also by their acquisitions of small biotechnology corporations with microbial product portfolios (Wilson and Jackson 2013). Bio-products containing antagonists of fungi and bacteria rank high among other bio-nematicides (Askary 2015a, b;Eissa and Abd-Elgawad 2015). As such nematicides represent living systems, a number of difficulties exist to develop commercial bio-nematicidal products.…”
Section: Brinjalmentioning
confidence: 99%
“…Importance of biological control of pests is growing, and this is obviously reflected by considerable venture capital in research by multinational firms and also by their acquisitions of small biotechnology corporations with microbial product portfolios (Wilson and Jackson 2013). Bio-products containing antagonists of fungi and bacteria rank high among other bio-nematicides (Askary 2015a, b;Eissa and Abd-Elgawad 2015). As such nematicides represent living systems, a number of difficulties exist to develop commercial bio-nematicidal products.…”
Section: Brinjalmentioning
confidence: 99%
“…have a considerable effect as biocontrol agents on plant-parasitic nematodes (PPNs) and on root colonization, multiple modes of action, and promising ability to sporulate under stressed conditions (Kavitha et al 2012). Nematophagous bacteria as biocontrol agents of PPNs were recently reviewed (Eissa and Abd-Elgawad 2015). Abd-El-Khair et al (2016) showed that eight selected isolates of Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Molinari et al [77] reported no effects on CAT activity in nematode-susceptible cultivars. Contrarily, Eissa et al [78] suggested that nematode-resistant cultivars without inoculation had a higher concentration of CAT than susceptible cultivars. This contradiction might be due to the fact that the nematode population did not reach a certain level where CAT activity could be highly reduced.…”
Section: Discussionmentioning
confidence: 99%